2022
DOI: 10.3390/ijerph19010552
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesizing in the Face of the Opioid Crisis Coupling Genetic Addiction Risk Severity (GARS) Testing with Electrotherapeutic Nonopioid Modalities Such as H-Wave Could Attenuate Both Pain and Hedonic Addictive Behaviors

Abstract: In the United States, amid the opioid overdose epidemic, nonaddicting/nonpharmacological proven strategies are available to treat pain and manage chronic pain effectively without opioids. Evidence supporting the long-term use of opioids for pain is lacking, as is the will to alter the drug-embracing culture in American chronic pain management. Some pain clinicians seem to prefer classical analgesic agents that promote unwanted tolerance to analgesics and subsequent biological induction of the “addictive brain”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…Although there is a moderate-to-strong effect of the HWDS in offering pain relief, reduction in pain medication usage, and improved function as reported in this study, additional studies are warranted. The best result was noted for improved function, indicating that the HWDS can lead to a speedier return to work and other associated daily activities [ 33 , 34 , 35 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a moderate-to-strong effect of the HWDS in offering pain relief, reduction in pain medication usage, and improved function as reported in this study, additional studies are warranted. The best result was noted for improved function, indicating that the HWDS can lead to a speedier return to work and other associated daily activities [ 33 , 34 , 35 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Most relevant to these important caveats to relieve pain is to embrace electrotherapy such as H-Wave ® device stimulation (HWDS), whereby there is significant evidence that its prescribed utilization could be a very useful tool instead of powerful opioids [ 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our "out of the box" novel approach requires the coupling of genetic risk polymorphic testing with the safe and wellstudied complex KB220 or KB220Z customized to match the presence of resultant alleles and, as such, provides a precision nutraceutical known to have pro-dopamine regulatory pharmacological properties, including H-Wave therapy (19). There is a plethora of high-tier publications providing unequivocal evidence to establish a common overlap neuro-mechanism between substance and nonsubstance addiction (alcohol, opioids, food, etc.)…”
Section: Snapshot Review Of Evidencementioning
confidence: 99%
“…In fact, in terms of major depression, transcriptome-wide association research analyses of major depression indicated significant correlations with the expression of DRD2 in the nucleus accumbens (NAc) and NEGR1 in the hypothalamus, among others. However, our laboratory has adopted an alternative approach involving finite pathways as candidates instead [ 19 ].…”
Section: Introductionmentioning
confidence: 99%